Tax Revenue Rate During the Pandemic Covid 19 in Medan City: Evidence from KPP Medan - Edisah Putra Nainggolan; Seprida Hanum Harahap; Ikhsan Abdullah; Nadia Ika Purnama; Nel Arianty (Institute of Computer Science (IOCS), 2022)
This study aims to see how the people of Medan complied during the Covid-19 pandemic in fulfilling their tax obligations. In terms of tax compliance, the author assesses the aspect of awareness and also the services provided by the Medan City Government. This study took samples from the Medan City Primary Tax Service Office with a total sample of 100 people. By using the Multiple Linear Regression data analysis technique. The results of the study found that taxpayer awareness has an effect on tax compliance and services affect tax compliance. Simultaneous testing produces awareness results and also services have a simultaneous effect on compliance with paying taxes during the covid 19 pandemic in Medan City.